IMPROVING BALINESE LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF PRAGMATIC APPROACHES - Anggreni, Ni Made Ayu Dwi (Indonesian Journal of Educational Development (IJED), 2023)
This research is a classroom action research consisting of 2 cycles. The research subjects were all 34 students of Class X IPS 3 at SMA Negeri 1 Kuta. The objectives of this study included: 1) to know student learning outcomes in learning Balinese with the application of pragmatic learning approaches, 2) to know students' responses to learning Balinese with the application of pragmatic learning approaches. The results showed: 1) student learning outcomes increased and 2) students gave positive responses to Balinese language subject. In cycle I, student learning outcomes obtained an average class of 74.71 with classical completeness of 82.35% in the incomplete category. In cycle II, student learning outcomes obtained a class average of 80.74 with classical completeness of 94.12% in the complete category. Based on the results of this study, the application of a pragmatic approach can be used as an alternative in an effort to improve the quality of student learning processes and outcomes.